Maternal 25-Hydroxyvitamin D Deficiency Promoted Metabolic Syndrome and Downregulated Nrf2/CBR1 Pathway in Offspring - Jianqiong Zheng; Jianqiong Zheng; Xiaohui Liu; Bingbing Zheng; Zhenzhen Zheng; Hongping Zhang; Jiayong Zheng; Congcong Sun; Haiying Chen; Jie Yang; Zuo Wang; Meimei Lin; et al. (Frontiers Media S.A., 2020)
Metabolic syndrome is a disorder of energy use and storage, which is characterized by central obesity, dyslipidemia, and raised blood pressure and blood sugar levels. Maternal 25-hydroxyvitamin D deﬁciency is known to cause metabolic changes, chronic disease, and increased adiposity in adulthood. However, the underlying mechanism of induced metabolic syndrome (MetS) in the offspring in vitamin D deficient pregnant mothers remains unclear. We identified that maternal 25-hydroxyvitamin D deficiency enhances oxidative stress, which leads to the development of MetS in the mother and her offspring. Further, immunohistochemical, Western blotting, and qRT-PCR analyses revealed that maternal 25-hydroxyvitamin D deficiency inhibited the activation of the Nrf2/carbonyl reductase 1 (CBR1) pathway in maternal placenta, liver, and pancreas, as well as the offspring's liver and pancreas. Further analyses uncovered that application of 25-hydroxyvitamin D activated the Nrf2/CBR1 pathway, relieving the oxidative stress in BRL cells, suggesting that 25-hydroxyvitamin D regulates oxidative stress in offspring and induces the activation of the Nrf2/CBR1 pathway. Taken together, our study finds that maternal 25-hydroxyvitamin D deficiency is likely to result in offspring's MetS probably via abnormal nutrition transformation across placenta. Depression of the Nrf2/CBR1 pathway in both mothers and their offspring is one of the causes of oxidative stress leading to MetS. This study suggests that 25-hydroxyvitamin D treatment may relieve the offspring's MetS.